The Effect of Service Quality on Consumer Trust and Customer Satisfaction to Improve Customer Loyalty on Go-Car Transportation Online in Semarang City - Candra Alfiyanto; Farida Indriani; Mirwan Surya Perdhana (Universitas Diponegoro, 2020)
This study aims to analyze the Effect of Service Quality on Consumer Satisfaction and Consumer Confidence in Improving Consumer Loyalty of Go-Car Online Transportation Services in Semarang City, by using variables of service quality, customer satisfaction, consumer trust and customer loyalty are expected to know the level of users of transportation service Go Car online. In analyzing the data in this study using a quantitative approach to the method of analyzing structural equation models (SEM) using AMOS software on 96 respondents who have been determined to become research respondents through non-probability sampling techniques. This study consists of four hypotheses proposed, the results of the study prove that 1) service quality has a positive and significant effect on customer satisfaction, 2) service quality has a positive effect on Consumer Confidence, 3) customer satisfaction has a negative effect on Consumer Loyalty, 4) Service Quality has an effect negative to Consumer Loyalty, 5) Customer Trust negatively affects Consumer Loyalty.